3D-printing of adsorbents for increased productivity in carbon capture applications (3D-CAPS). (December 2021) - Sluijter, S.N.; Boon, J.; James, J.; Krishnamurthy, S.; Lind, A.; Blom, R.; Andreassen, K.A.; Cormos, A.M.; Sandu, V.C.; de Boer, R.
Highlights: CO2 adsorbents are structured by 3D-printing to improve productivity (kg CO2 /m 3 hr). CFD model to predict the performance of 3D-printed sorbents has been validated. CO2 adsorbents maintain adsorption capacity after 3D-printing. Pressure drop and mass transfer improvement structures are proven experimentally. Significant increase in productivity by 3D-printed confirmed by multi-cycle modelling. Abstract: An important driver in the development of adsorption-based CO2 capture technologies is the reduction of cost through increasing the productivity. The 3D-CAPS project aims to increase the productivity (kg CO2 /m 3 hr) of such technologies through structuring, enabled by 3D-printing. This productivity increase would allow for a reduction of the size of the adsorbers and the associated CAPEX and/or energy requirements. Pre-combustion, as well as post-combustion technologies, are investigated using potassium-promoted hydrotalcite (K-HTC) for sorption-enhanced water-gas shift (SEWGS) and amine-functionalized silica (ImmoAmmo) as sorbents, respectively. This contribution presents a technical overview highlighting several aspects of the project ranging from CFD modelling to assess the shape of the sorbents, 3D-printing of the sorbent materials as well as testing of the ImmoAmmo sorbent for post-combustion capture applications. It is discussed how several essential elements of the productivity improvement have been separately proven in the 3D-CAPS project, both by modelling and experimentally: maintained adsorption capacity upon 3D-printing, reduced pressure drop, and improved mass transfer.